Unusual Lesion in the Splenium of the Corpus Callosum and COVID-19 Infection: A Case Report. Issue 1 (6th February 2023) - Abid, Wiem; Vanderhasselt, Tim; Allemeersch, Gert-Jan
The novel coronavirus (SARS-CoV-2) causing the recent pandemic outbreak may result in brain injuries. The disease has a high prevalence for thromboembolic complications and a massive release of cytokines. We report a case of CLOCCS, one of the rare neurological complications of SARS-CoV-2 infection. Teaching Point: The imaging features of the cytotoxic lesion of the corpus callosum (CLOCCS) on magnetic resonance imaging should be known by every radiologist, to make the positive diagnosis and prevent misdiagnosis, especially in the setting of a COVID-19 infection.